Ответы и объяснения

Лучший Ответ!
2012-12-30T17:00:48+00:00

4x^2+8x=4x(x+2)

3m-6m+mn-2n^2=(n+3)(m-2n)

9a^2-16=(3a-4)(3a+4)

y^3+18y^2+81y=y(y^2+18y+81)=y(y+9)^2

 

\frac{36-a^2}{18+3a}=\frac{(6-a)(6+a)}{3(6+a)}=\frac{6-a}{3}\\\frac{9p^2-q^2}{9p^2+6pq+q^2}=\frac{(3p-q)(3p+q)}{(3p+q)^2}= \frac{3p-q}{(3p+q)}

 

 x^3-36x=0

x(x^2-36)=0

x(x-6)(x+6)=0

1)x=0

2)x-6=0

x=6

3)x+6=0

x=-6

 

x^2+14x+48=(x+6)(x+8)

x^2+14x+48=x^2+8x+6x+48

x^2+14x+48=x^2+14x+48

x^2+14x+48-x^2-14x-48=0

0=0

 

\frac{169^3+59^3}{228}-169*59=\frac{(169+59)(169^2-169*59+59^2)}{228}-169*59=\\\frac{228(169^2-169*59+59^2)}{228}-169*59=169^2-169*59+59^2-169*59=\\169^2-2*169*59+59^2=(169-59)^2=110^2=12100